On the Study of Mongolian Script Lexicography - Jantsan, Bat-Ireedui (Mongolian Journal of Applied Linguistics, 2023)
In this article, the history of lexicography of Mongolian linguistics, including the lexicography of Mongolian writing, is discussed. Mongolian linguistics has a rich history of lexicography, including the study of dictionaries based on knowledge of the Mongolian Cyrillic alphabet for Mongolian language learners since the 1990s. Although these dictionaries have different authors, they are essentially the same and differ in some ways. In this way, creating a dictionary of Mongolian script based on the Mongolian Cyrillic script seems to be convenient for students on the one hand, but on the other hand, it may be a hindrance. In the future, it is necessary to create a dictionary of Mongolian scripts in Classical Mongolian. Монгол бичгийн толь бичиг судлалын тухай асуудалд Хураангуй: Энэ өгүүлэлд монгол хэл шинжлэлийн түүхэн дэх монгол бичгийн толь бичгийн уламжлал, шинэчлэл, ялангуяа ерээд оноос хойш Монгол Улсад хэвлэгдсэн монгол бичгийн толь бичгүүдийн бүтэц, арга зүй, онцлогийн талаар судлан шинжилсэн тухай дурдах болно. Түлхүүр үг: монгол хэл шинжлэл, монгол толь бичиг, монгол бичиг, монгол хэлний зөв бичих дүрэм, толь бичгийн бүтэц, агуулга, хэрэглээ